Does government support for private innovation matter? Firm-level evidence from Turkey and Poland - Wojciech Grabowski; Teoman Pamukcu; Krzysztof Szczygielski; Sinan Tandogan (Center for Social and Economic Research (CASE), 2013)
The aim of the project is to analyze government support for innovation in a comparative perspective by first examining the main existing instruments of financial support for innovation in Turkey and Poland, and secondly to assess their effectiveness by applying recent econometric techniques to firm-level data for both countries obtained from the Community Innovation Survey (CIS). Comparing Turkey to Poland is both meaningful and promising from a policy-analysis point of view. Both countries are comparable in terms of levels of economic development and technological capabilities, i.e. the ability of their economies to create knowledge and exploit it commercially. Both have undergone deep market-oriented reforms in the last decades - Turkey since 1980, Poland since 1989 - resulting in a significant catching-up of their economies. However, as the possibilities for further growth based on structural change and eliminating obstacles to business are shrinking, the problem of building a knowledge-based economy comes to the fore.
Keywords: O31; O38; H81; 330; Innovation; Manufacturing Firms; Government Support; EU Structural Policy; Poland; Turkey